Comparative Analysis of High-Strength Concrete Cylinders Reinforced with Varied Configurations of Carbon Fibre Reinforced Polymer Strips - Michelleine Michael; Ahmad Zakwan, Fariz Aswan; Ismail, Ruqayyah; Ahmad, Hazrina; Wahid, Norlizan; Hashim, Nor Hafida (International Journal of Sustainable Construction Engineering and Technology, 2024)
Concrete, a material renowned for its robustness, flexibility, and cost-efficiency, is ubiquitously employed in a multitude of structural applications. Among its variants, High Strength Concrete (HSC), characterized by a compressive strength exceeding 40 MPa, has emerged as a focal point of interest in contemporary structural engineering research. The incorporation of Carbon Fibre Reinforced Polymer (CFRP), a high-strength composite material, as a strengthening agent in HSC structures represents a novel approach in the field. This study embarks on a comprehensive investigation to assess the efficacy of different configurations of CFRP strips in augmenting the strength of HSC cylinders. A total of fifteen HSC cylinders, each reinforced with a unique configuration of CFRP strips, were subjected to rigorous testing. The cylinders, cast using a standard mould, measured 150 mm in diameter and 300 mm in length. The experimental results revealed a significant enhancement in the strength of the CFRP-reinforced cylinders. Notably, cylinders reinforced with horizontal CFRP strips exhibited an increase in strength of approximately 68% compared to the unconfined specimens. This substantial increase underscores the potential of horizontal CFRP strip configuration in optimizing the strength of HSC structures. Moreover, an analysis of the stress-strain behaviour of the CFRP-reinforced cylinders yielded insightful findings. Both the stress and strain behaviours of the CFRP-reinforced cylinders, irrespective of the CFRP strip configuration, surpassed those of the unconfined specimens. This observation affirms the role of CFRP strips in not only enhancing the strength but also improving the overall mechanical performance of HSC cylinders. In conclusion, the findings of this study unequivocally demonstrate that CFRP strips significantly enhance the strength of HSC cylinders. The results underscore the potential of CFRP strips, particularly in horizontal configuration, for widespread application in structural engineering, paving the way for more resilient and efficient concrete structures. Future research could explore the impact of varying the thickness and material properties of the CFRP strips to further optimize the performance of HSC structures.